Kartki z historii filologii klasycznej w Warszawie 1. Korespondencja Gustawa Przychodzkiego z Albertem C. Clarkiem, 1920-1925 - Mejor, Mieczysław (Colloquia Litteraria, 2009)
Pages of the history of classical philology in Warsaw. The correspondence of Gustaw Przychodzki and Albert C. Clark, 1920-1925 This is the first in a series of articles presenting a selection of correspondence of professor Gustaw Przychodzki, who founded the Institute of Classical Studies in the newly revived University of Warsaw in 1919. Professor Albert C. Clark’s letter from Oxford dated 1920 is the first to be published. It was written when Poland was experiencing the dramatic moment of powerful Bolshevik armed forces approach to Warsaw. Gustaw Przychodzki was then fighting on the front. Professor Clark expressed his joy at the revival of classical studies in Warsaw and wished all Poles success in defending the city against the Bolsheviks.